Clinical ethics support services in the UK: an investigation of the current provision of ethics support to health professionals in the UK. (1st April 2001) - Slowther, Anne; Bunch, Chris; Woolnough, Brian; Hope, Tony
Abstract : Objective—To identify and describe the current state of clinical ethics support services in the UK. Design—A series of questionnaire surveys of key individuals in National Health Service (NHS) trusts, health authorities, health boards, local research ethics committees and health professional organisations. Interviews with chairmen/women of clinical ethics committees identified in the surveys. Setting—The UK National Health Service. Results—Responses to the questionnaires were received from all but one NHS trust and all but one health authority/board. A variety of models of clinical ethics support were identified including twenty formal clinical ethics committees (CECs). A further twenty NHS trusts expressed an intention to establish a CEC within the next twelve months. Most CECs in the UK have been in existence less than five years and are still defining their role. The chairmen identified education of committee members and contact with other ethics committees as important requirements for committee development. Problems were identified around lack of support for the committee and with raising the profile of the committee within the institution. There has been little evaluation of clinical ethics support services either in the UK or in other countries with longer established services. What evaluation has occurred has focused on process rather than outcome measures. Conclusions—Clinical ethics support services are developing in the UK. A number of issues have been identified that need to be addressed if such support services are to develop effectively.